Highly Transparent, Conductive, and Mechanically Robust Hydrogels via Rapid In Situ Synthesis for Flexible Electronics - W. Yuan; J. Zhao (Advanced Electronic Materials, 2025)
Abstract Hydrogels face challenges as flexible electronic materials, including complex preparation processes and difficulty in balancing frost resistance, water retention, and mechanical properties. Here, a cost‐effective and efficient strategy for in situ rapid synthesis of hydrogels with Mo2C‐derived molybdenum polyoxometalates (POM) is developed. The Mo‐POM/ammonium persulfate (APS) redox pair enables rapid initiation of in situ free radical polymerization at room temperature, effectively addressing the limitations associated with conventional photo‐ or thermally‐initiated methods. The tunable redox activity of Mo‐POM allows precise control of polymerization time. This synthesis strategy utilizes the “freezing effect” achieved through rapid polymerization to achieve a uniform distribution of hydrogel components. Additionally, the incorporation of Mo‐POM and sodium alginate (SA) introduces diverse intermolecular interactions within the hydrogel network, significantly enhancing mechanical properties. LiCl incorporation provides exceptional frost resistance, water retention, durability, and stability even under prolonged load cycling. Furthermore, the hydrogel demonstrates outstanding electromechanical properties, reliably and rapidly responding to both large and subtle motions. This tunable synthesis strategy successfully balances mechanical and electromechanical performance, antifreeze capability, water retention, and durability. Consequently, it offers a promising approach for large‐scale, cost‐effective industrial production of high‐performance hydrogels.